A targeted sequencing reveal overlapping pattern of genetic variants in patients with cardiomyopathy with cardiac arrhythmias in Kazakhstan - Akilzhanova, A.; Guelly, Ch.; Abilova, Zh.; Rakhimova, S.; Akhmetova, A.; Kairov, U.; Nuralinov, O.; Rashbayeva, G.; Trajanoski, S.; Zhumadilov, Zh.; Bebosynova, M. (My University, 2016)
Ventricular tachycardia (VT) is a common symptom in cardiac disorders of different etiology. Abnormalities of ion channels are attributed to mutations in the genes encoding the channel protein and cause altered function of channels, which can predispose to arrhythmias. Due to the high incidence of cardiovascular disorders in Kazakhstan, we enrolled a study cohort of 95 patients of different clinical phenotypes of cardiomyopathies, including DCM, idiopathic VT but also patients with myocardial infarction as a consequence of coronary heart disease. The common denominator among the three main groups was the occurrence of severe episodes of VT in all patients. Using targeted resequencing, we investigated 96 cardiomyopathy associated candidate-genes in this cohort with the aim to detect rare and common variations in these genes associated with VT molecular basis
Keywords: targeted sequencing; cardiac arrhythmias; HaloPlex cardiopanel